Correction: Synthesis and X-ray structural characterization of the (chlorochalcogeno)phosphonium cations R2R′PSCl+ and R2R′PSeCl+ as their AuCl4− salts. Issue 45 (13th November 2017) - Upmann, Daniel; Jones, Peter G.
Abstract : Correction for 'Synthesis and X-ray structural characterization of the (chlorochalcogeno)phosphonium cations R2 R′PSCl + and R2 R′PSeCl + as their AuCl4 − salts' by Daniel Upmann and Peter G. Jones, Dalton Trans., 2013, 42, 7526–7528.